The relationship between dental caries and dental fluorosis in areas with moderate- and high-fluoride drinking water in Ethiopia - Wondwossen F, A ° strøm AN, Bjorvatn K, Ba° rdsen A. (Blackwell Synergy)
The aim of the study is to assess the relationship between caries and dental fluorosis in Ethiopian children living in Rift Valley areas known for endemic fluorosis.